Sensitivity and specificity of different exercise oscillatory ventilation definitions to predict 2-year major adverse cardiovascular outcomes in chronic heart failure patients. (1st August 2022) - Ribeiro, Gustavo dos Santos; Deresz, Luís Fernando; Salvioni, Elisabetta; Hansen, Dominique; Agostoni, Piergiuseppe; Karsten, Marlus
Abstract: Background: Exercise oscillatory ventilation (EOV) shows a four-fold greater risk of adverse events. This study aims to analyze the sensitivity and specificity of three EOV diagnostic definitions to predict adverse outcomes at a 2-year follow-up and to compare its EOV prevalence and relations with the patient's profile. Methods: Cardiopulmonary exercise tests from 233 heart failure patients were analyzed. Two blinded reviewers used a semiautomated software to identify EOV cases pattern according to the definitions of Ben-Dov, Corrà, and Leite. Data were grouped in EOV-positive or EOV-negative according to each definition. Baseline characteristics, EOV prevalence, relative risk, sensitivity, and specificity to predict 2-years of major adverse cardiovascular outcomes were analyzed. Results: The Corrà definition led to the best prediction of 2-year major cardiovascular adverse outcomes (HR 2.46 [1.16 to 5.25]; p  = 0.019, AUC = 0.618; p  = 0.007). EOV prevalence was 17.2%, 17.2%, and 9.4% applying Ben-Dov, Corrà, and Leite definition, respectively. The main clinical differences between EOV-positive and EOV-negative patients were: MECKI score and VE/VCO2 slope (all definitions), and BNP levels (Ben-Dov and Leite). BNP levels were correlated with amplitude ( rho  = 0.255; p  = 0.033) and cycle length ( rho  = 0.388; p  = 0.002). Conclusion: Corrà definition was the only one that exhibited the capacity to predict major adverse cardiovascular outcomes at a 2-year follow-up. Regardless of its definition, EOV was more often prevalent in patients with a greater MECKI score and VE/VCO2 slope values. Highlights: Exercise oscillatory ventilation is a phenomenon associated with a worse prognosis. There is no consensus on the best EOV definition to be applied. EOV prevalence is higher when Ben-Dov or Corrà definitions are applied. BNP levels are associated with amplitude and cycle length. Corrà definition has the better capacity to predict 2-year mortality. Graphical abstract: Unlabelled Image